The impact of the reserve requirement ratio in the activity of the bank credit: Applied Research in a sample of Iraqi private banks (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The research topic (The Impact of the Compulsory Reserve on the Banks Credit-an applied  research on    a sample of Iraqi banks), was chosen on basis of the Iraqi  private Banks attempts to increase their credit activities in hope to gain more profits.This coincided with  the CBI aim to back the private banking market.It is thus apparent why the CBI issued its regulation to those banks to increase their capitals up  to IDB250. On the other hand,the CBI acted as an obstacle in the way of increasing the private banks of their capitals,that is by implementing the quantitive  monetary tool  so called the compulsory reserve.This is why we intended to overlook at this contradictional  problome and try to resolve it and explore the effect of such tool on the credit activities of the banks under issue(Baghdad Bank,The Bank of the MidlleEast,Sumer Bank, North bank and  Ashour  Bank).The research was based on two hypothesis:1-The ratio of the CR(compulsory reserve) has a moral   and a statistical effect on the cash credit ,   investments and some monetary indications  of the banks under issue.2-The ratio of the CR has no moral or statistical effect on cash credit,investment and some monetary indications of the banks under issue. The  research contains four chapters:1-The first chapter deals with the contents of the research,(plus  some of previous studies).2-The second chapter deals with the theoretic aspects of the research with its three   components (The centra  bank ,the  monetary policy and the banks credit).3-The third   chapter   focused on knowing the effect.4-The fourth chapter   was the conclusion chapter. The conclusions showed ,in general and according to the statistical analysis, a  moral relation between the CR , the cash credit rendered and the investments in the subject banks( with The bank of the  midlle  East as an exception where this relation was also shown in the recruitment  indication).On the other hand no such relations were   shown   as a result of the statistical analysis  in other banks.The research came out with some recommendations like:The CBI must find it appropriate to mix the CR tool with other tools  in order to guide and orient  the credit activities  of the banks ,specially  in the countries that lack advanced money markets .Also  the CBI must enlarge and widen the contents of  the items which are subject to the implementation of the CR .